A Study of Intertextuality in Peter Ackroyd `s Selected Novels - Ameer Hussein (آداب الكوفة, 2023)
The concept of intertextuality is a central notion in postmodern theory and an important model to describe the relation between literary texts. The central  purpose of this paper is to scrutinize  the idea of intertextuality in postmodern theory and how it is manifested by the British prolific novelist Peter Ackroyd `s selected novels. The English critic and novelist of more than a dozen of novels as well as the  Booker Prize for Fiction. Ackroyd is a great example of English novelist who rewrites in his novels English literary history through  using the notion of intertextuality. As a result, Ackroyd`s novels are significant  of shoot of postmodern novel since they document the literary texts of earlier authors to become the subject of their plots which reflect the postmodern idea in which literary works are viewed to mirror other works . Therefore, Ackroyd`s novels can be regarded as unique versions of this trend of  postmodern fiction as well as literary criticism.  The concept of intertextuality becomes subject to adaptation and revision in postmodern literary theory.